MATSKEVICH BOLESLAV IOSIFOVICH – PEDIATRIC SURGEON, TEACHER, SCIENTIST (TO THE 90TH ANNIVERSARY OF HIS BIRTHDAY) - Shejbak, V. M.; Kovalchuk, V. I. (Zhurnal Grodnenskogo gosudarstvennogo medit͡s︡inskogo universiteta, 2018)
The article presents the basic vital stages of medical, scientific, pedagogical and public activity of the doctor of medical sciences, professor Boleslav Iosifovich Matskevich.